ONLINE-BASED QUIZ MAKING TRAINING FOR MATHEMATICS TEACHERS OF SMA NEGERI 3 PADANG DURING THE PANDEMIC - Ainil Mardiyah; Hafizah Delyana; Lita Lovia; Ali Asmar (RANGKIANG: Jurnal Pengabdian Pada Masyarakat, 2020)
The world of education is currently experiencing a very extraordinary event. The Covid-19 pandemic has a very broad impact on participants and educational institutions. Our education system must be ready to take the leap to transform online learning for all students and by all teachers. We are entering a new era to build creativity, hone student skills, and improve our quality with changes in systems, perspectives and patterns of our interactions with technology. Every individual who is in an educational environment must be able to use technology that can help the learning process, especially in schools. Likewise, with the implementation of teaching and learning at SMAN 3 Padang, the process of implementing learning in these schools currently cannot be carried out face-to-face in class as usual. Students take lessons from home. To find out the ability of teacher students, they must evaluate the learning that has been given. One of them is by giving the teacher online quizzes because face to face is no longer possible during the Covid 19 pandemic. Mathematics is one of the subjects considered difficult by students, especially for mastery of Olympic questions. For this reason, teachers are required to have creativity so that learning can be understood by students. Mathematics teachers are given training that supports this. The training that will be provided is in the form of making questions for quizzes which are carried out online. The students will solve these questions in accordance with the specified time. Teachers who take part in the training are expected to be able to motivate and evaluate students' ability to work on Olympic questions even though they are carried out online.